Aetiopathogenesis, clinico-epidemiological and diagnostic aspects of human ocular trematode infections: a scoping review protocol - Harshi Weerakoon; Kosala Weerakoon; Piyumi Kodithuwakku; Anjana Silva; Susiji Wickramasinghe (BMJ Open)
Introduction Human ocular trematode infections, caused by parasitic flatworms, are a significant public health concern worldwide. It can lead to mild-to-severe consequences if untreated. This protocol outlines a scoping review methodology, which aims to explore the knowledge on the aetiopathogenesis, clinico-epidemiological and diagnostic aspects, and patient perspectives related to ocular trematode infections in humans.Methods and analysis The review, including the development of the review protocol, will be conducted over 2 years from January 2024. The Joanna Briggs Institute Reviewers’ Manual and the framework developed by Arksey and O’Malley will be used as the guidelines for the scoping review that is suggested in this protocol. Accordingly, the PCC (Population, Concept, Context) framework and three-stage search strategy will be used to develop the research question and to conduct the search respectively. Publications up to December 2024 will be searched across multiple databases, including MEDLINE/PubMed, Scopus, Science Direct, CINAHL and Google Scholar.Ethics and dissemination Since the study will make use of secondary data, ethical approval will not be required. The scoping review’s findings will be published in a scientific journal and presented at relevant conferences, aiming to improve the disease outcomes through guiding future research in ocular trematode infections and informing potential strategies to uplift the disease control and prevention measures and patient care.